Effectiveness of naked eye single tube osmotic fragility test for screening of β-thalassemia trait from north Maharashtra region, India - Ismail, Mohammad; Patel, Nisar G. (International Journal Of Community Medicine And Public Health, 2017)
Background: Thalassemia’s are serious public health problem in all over the world. Different techniques are used for the diagnosis of different types of thalassemia’s which are costly and time consuming. This study was aimed to determine the efficacy of naked eye single tube osmotic fragility test as a screening test for β-thalassemia trait and to standardize a saline concentration which could give best results with maximum sensitivity and specificity. Methods: Three different buffered saline concentrations (0.32%, 0.34% and 0.36%) were used. The test was applied to blood samples of 1702 family members from 130 β-thalassemia major patients. Results: The test results was compared and on the basis of our findings, recommend the use of 0.36% buffered saline. The test was positive in 589/629 subjects with β-thalassemia traits. The sensitivity of the test was 93.6% and specificity was 89.1%. There were 10.9% false positive results in hematologically normal subjects. The test also gave positive results with 3/13 α-thalassemia and 20/24 double heterozygous sickle/β-thalassemia. Conclusion: The test was proved to be useful in areas with high frequency of hemoglobinopathies and found simple, cheap and adaptable in under-resourced laboratories. However, it cannot replace red cell indices generated by automatic electronic cell counters.